2014
DOI: 10.1002/masy.201300166
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a Bis(imine)Pyridine Iron Catalyst System in Ethylene/Norbornene Copolymerization with Zinc Diethyl

Abstract: Summary Brookhart catalysts are widely used in ethylene polymerization to produce polymers with high molecular weight and crystallinity degree. In the present work, the performance of a bis(imine)pyridine iron catalyst and methylaluminoxane (MAO) as a catalytic system was evaluated for ethylene/norbornene copolymerization and the influence of adding zinc diethyl (DEZ) in the reaction medium was investigated. The results showed that the system was effective in copolymerization besides the low incorporation of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…19 The addition of CTAs increased the catalytic activity, 19 while molar mass and norbornene content decreased, which is in agreement with the previous observations (Table 2). 20 The possibility of chain transfer from salicylaldimine or αdiimine late transition metal complexes to various metal alkyls during ethene polymerization was thoroughly investigated. 21 Initial screening revealed that only α-diimine Ni complexes (11a−c, Figure 3), in the presence of Zn based CTAs, are capable of providing efficient chain transfer.…”
Section: Coordinative Chain Transfer Polymerizationmentioning
confidence: 99%
See 3 more Smart Citations
“…19 The addition of CTAs increased the catalytic activity, 19 while molar mass and norbornene content decreased, which is in agreement with the previous observations (Table 2). 20 The possibility of chain transfer from salicylaldimine or αdiimine late transition metal complexes to various metal alkyls during ethene polymerization was thoroughly investigated. 21 Initial screening revealed that only α-diimine Ni complexes (11a−c, Figure 3), in the presence of Zn based CTAs, are capable of providing efficient chain transfer.…”
Section: Coordinative Chain Transfer Polymerizationmentioning
confidence: 99%
“…71,72 The addition of Et 2 Zn led to the molar mass decreasing and, a lower incorporation of norbornene (0.8−1.0 vs 1.6%, Table 2), while the overall catalytic activity was preserved. 20…”
Section: Mechanistic Studies and Extension Of Known Systemsmentioning
confidence: 99%
See 2 more Smart Citations